Application of Starch-Stabilized Silver Nanoparticles as a Colorimetric Sensor for Mercury(II) in 0.005 mol/L Nitric Acid. (13th April 2017) - Vasileva, Penka; Alexandrova, Teodora; Karadjova, Irina
Abstract : A sensitive and selective Hg 2+ optical sensor has been developed based on the redox interaction of Hg 2+ with starch-coated silver nanoparticles (AgNPs) in the presence of 0.005 mol L −1 HNO3 . The relative intensity of the localized surface plasmon absorption band of AgNPs at 406 nm is linearly dependent on the concentration of Hg 2+ with positive slope for the concentration range 0–12.5 μ g L −1 and negative slope for the concentration range 25–500 μ g L −1 . Experiments performed demonstrated that metal ions (Na +, K +, Mg 2+, Ca 2+, Pb 2+, Cu 2+, Zn 2+, Cd 2+, Fe 3+, Co 2+, and Ni 2+ ) do not interfere under the same conditions, due to the absence of oxidative activity of these ions, which guarantees the high selectivity of the proposed optical sensor towards Hg 2+ . The limits of detection and quantification were found to be 0.9 µ g L −1 and 2.7 µ g L −1, respectively, and relative standard deviations varied in the range 9–12% for Hg content from 0.9 to 12.5 μ g L −1 and 5–9% for Hg levels from 25 to 500 μ g L −1 . The method was validated by analysis of CRM Estuarine Water BCR505. A possible mechanism of interaction between AgNPs and Hg 2+ for both concentration ranges was proposed on the basis of UV-Vis, TEM, and SAED analyses.